Perancangan dan Pembuatan Aplikasi Penghubung antar Bahasa - Dhani Himawan Budiarto; Liliana Liliana; Anita Nathania (Jurnal Infra, 2017)
In this paper, we describe the formatting guidelines for ACM SIG Proceedings.  Communication is a process or a way to deliver a message from one person to another to achieve a certain goal. But often communications between individuals or groups are limited by differences of languages. Languages differences make it hard for people to convey an urge, convey intentions and goals. Until now, the world’s progress on technology has not given the way to bridge this issue as its main goal.With the development of scientific study of technology  that explore languages and communication, it is possible that differences in languages will not become an obstacle for people to communicate with one another. To solve this problem, an application is made to act as a translator between 2 person’s conversations. This application uses Android Studio and Java as its language.After the system testing is done, it could be concluded that the application is an effective tool to help user to get better understanding despite the language differences.